The Role of the Public Service Mall in the Perspective of Good Governance - Slamet Muchsin; Rini Rahayu Kurniati; Najib Shinwari; David J Griffiths; femia yuhandika (Universitas Merdeka Malang, 2025)
This study aims to examine the role of Merdeka Malang Public Service Mall (MPP) in supporting the implementation of good governance principles, particularly transparency, accountability, service efficiency, and public participation. The research employs a qualitative method with data collected through in-depth interviews, observations, and documentation. Informants include MPP staff, tenants from various agencies, and service users. The findings reveal that MPP Merdeka Malang successfully facilitates integrated services that simplify public access to various government and non-government services efficiently. Transparency and accountability are realized through open information mechanisms, supervision, and responsive complaint management. Public participation is also encouraged through consultation spaces and user satisfaction surveys. However, challenges such as inter-agency coordination and suboptimal digital integration need improvement. Overall, MPP Merdeka Malang has implemented the New Public Service (NPS) principles in its public service delivery and significantly contributes to good governance at the local level. This study recommends enhancing coordination, technological integration, and socialization to improve service quality and public participation